Eksistensi Syahbandar dalam Penegakan Hukum Pelayaran di Kota Ternate - Fathurrahim Fathurrahim (Faculty of Law, Khairun University, 2019)
The role of the shahbandar in the enforcement of shipping crime has the highest authority in conducting initial inspections of ship accidents with the aim of knowing the causes of ship accidents and / or determining whether or not there is an error or omission in the application of maritime professional standards carried out by the master or ship leader and / or Ship Officer in connection with a ship accident. The Role of Syahbandar in the Investigation of Sailing Crimes in the Case of Ship Accidents is not running optimally, this is due to inhibiting factors in terms of human resources in this case related to the limited number of personnel, education and training as well as facilities and facilities factors related to the minimal number of patrol vessels very significant in carrying out investigation of shipping crime in this case a ship accident in the waters.